A Comprehensive Survey On The Integration And Impact Of Innovative Pedagogy Techniques In Engineering Education (Journal of Namibian Studies : History Politics Culture, 2022)
The engineering syllabus in India, typically designed for a four-year undergraduate program, is indeed structured to provide students with a comprehensive education in engineering and related fields. Imbibing such a wide range of educational aspects within four years for differently-abled learners in a large classroom setting  limits the educational innovations, more specifically use of a wide spectrum of pedagogy techniques. Teacher education is itself rarely learner-centred and hence importance is given to teaching skills, patterns of school organization and curricular content rather than pedagogy.The acceptance of the innovative pedagogical techniques in engineering education, despite having numerous advantages,is doubtful and can only be confirmed by surveying the actual student and teacher experience in this regard.Survey instrument with instructor led pedagogy techniques and pedagogy techniques promoting self paced  learning was designed. Survey instrument consisting of 14 pedagogic techniques was circulated among 19 private affiliated engineering institutes across Maharashtra state of India. 1777 students and 221 teachers responded. The survey form was designed to record responses on 5 point likert scale (Never- Rarely- Sometimes-Often-Always).Descriptive analysis, Bivariate analysis and Factor analysis were performed..Research instruments were tasted and found reliable for both controlled groups i.e. students and teachers. By analyzing the survey responses it was found that the construct “Pedagogy” is  independent of all demographic variables. Survey analysis also suggested the improvement in inclusiveness of a variety of pedagogy techniques in engineering education.  According to both Student & Teacher survey; Classroom Games and Mathematical Puzzles were the least used pedagogy technique and Project is the most utilized pedagogic technique.